2018
DOI: 10.1093/jisesa/iey114
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Differential Gene Expression in Wing Polymorphism of Adult Males of the Largest Water Strider: De novo Transcriptome Assembly forGigantometra gigas(Hemiptera: Gerridae)

Abstract: Wing polymorphism is common in a wide variety of insect species. However, few studies have reported on adaptations in the wing polymorphism of insects at molecular level, in particular for males. Thus, the adaptive mechanisms need to be explored. The remarkable variability in wing morphs of insects is well represented in the water striders (Hemiptera: Gerridae). Within this family, Gigantometra gigas (China, 1925), the largest water strider known worldwide, displays macropterous and apterous males. In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 77 publications
0
1
0
Order By: Relevance
“…While male polymorphism is less frequent than sexual dimorphism, it is still relatively common across a wide array of animals, especially in social insects such as bees, wasps, ants, and termites (Cook, 2021; Ding et al, 2019; Heinze & Tfindl, 2005; Song et al, 2009; Xin et al, 2020). Moreover, non‐social insects like dragonflies, damselflies, spade beetles, water striders, and aphids have also been reported to exhibit male polymorphism (Futahashi, 2016; Matsumoto & Knell, 2017; Nomakuchi, 1992; Sun et al, 2018; Ziabari et al, 2023). Male polymorphism has also been found in Diptera, for example, Sciaridae (Steffan, 1973), Ulidiidae (Oliveira Vasconcelos et al, 2019), and Diopsidae (Baker et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…While male polymorphism is less frequent than sexual dimorphism, it is still relatively common across a wide array of animals, especially in social insects such as bees, wasps, ants, and termites (Cook, 2021; Ding et al, 2019; Heinze & Tfindl, 2005; Song et al, 2009; Xin et al, 2020). Moreover, non‐social insects like dragonflies, damselflies, spade beetles, water striders, and aphids have also been reported to exhibit male polymorphism (Futahashi, 2016; Matsumoto & Knell, 2017; Nomakuchi, 1992; Sun et al, 2018; Ziabari et al, 2023). Male polymorphism has also been found in Diptera, for example, Sciaridae (Steffan, 1973), Ulidiidae (Oliveira Vasconcelos et al, 2019), and Diopsidae (Baker et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Among gerrids and "veliids" there are macropters, brachypters, micropters and apters, depending on the species. SUN et al (2018) described gene expression differences between the macropterous and brachypterous form of the gerrid Gigantometra gigas Hungerford & Matsuda, 1958. Unfortunately, there isn't any comprehensive knowledge on the genetic and ontogenetic processes leading to the wing polymorphism of any gerromorph species. Experimental works have been demonstrated that a considerable part of the wing polymorphism of different gerrid species is heritable (VEPSÄLÄINEN 1974a, 1978: ZERA et al 1983SPENCE and ANDERSON 2003).…”
Section: Review Of the Wing Dimorphism/polymorphism Of The Different ...mentioning
confidence: 99%